Contested Transparency: Digital Monitoring Technologies and Worker Voice - Filippo Belloc; Gabriel Burdin; Stefano Dughera; Fabio Landini (Institute of Labor Economics (IZA), 2023)
Advances in artificial intelligence and data analytics have notably expanded employers' monitoring and surveillance capabilities, facilitating the accurate observability of work effort. There is an ongoing debate among academics and policymakers about the productivity and broader welfare implications of digital monitoring (DM) technologies. In this context, many countries confer information, consultation and codetermination rights to employee representation (ER) bodies on matters related to the workplace governance of these technologies. Using a cross-sectional sample of more than 21000 European establishments, we document a positive association between ER and the utilization of DM technologies. We also find a positive effect of ER on DM utilization in the context of a local-randomization regression discontinuity analysis that exploits size-contingent policy rules governing the operation of ER bodies in Europe. Finally, in an exploratory analysis, we find a positive association between DM and process innovations, particularly in establishments where ER bodies are present and a large fraction of workers perform jobs that require finding solutions to unfamiliar problems. We interpret these findings through the lens of a labor discipline model in which the presence of ER bodies affect employer's decision to invest in DM technologies.
Keywords: M5; J50; O32; O33; 330; digital-based monitoring; algorithmic management; HR analytics; transparency; innovation; worker voice; employee representation